Conceptual images and learning obstacles in exponentiation and logarithms: A hermeneutic phenomenological analysis - Kusumadewi, Yuvita Andriani; Andriatna, Riki (Universitas Hamzanwadi, 2024)
The concept of exponentials and logarithms is one of the essential concepts in mathematics as part of transcendent functions. However, students' understanding of these two concepts has yet to be fully mastered, so there are still errors in solving problems related to these two concepts. This study aims to describe the meaning and meaning process and explore the potential learning obstacles of students based on the meaning and experience of students in obtaining the meaning of exponents and logarithms in senior high school. This qualitative study uses a hermeneutic phenomenological approach with student participants and high school mathematics teachers. Data was collected using tests, documentation, and interviews with students and teachers. Data were analyzed qualitatively to identify learning obstacles and the meaning of exponentials and logarithms. The results showed the meaning of exponents and logarithms according to students, namely exponents as power numbers and logarithms as the opposite of power numbers. In addition, the results also show the existence of learning obstacles in students, both ontogenic, epistemological, and didactic. Based on the findings, these learning obstacles can be considered when developing an appropriate didactic design.